All-solid-state stretchable supercapacitor based on double network gel and preparation method thereof
By growing the electrode active material on the dual network gel matrix, the problem of poor contact between the electrode and the electrolyte interface of the all-solid-state stretchable supercapacitor electrode is solved, and low charge transfer resistance and excellent cycling stability are achieved.
Patent Information
- Application Number
- CN202111616162.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-27
AI Technical Summary
The existing all-solid-state stretchable supercapacitors have poor contact at the interface between the electrode and the solid electrolyte, resulting in an increase in charge transfer resistance, a decrease in effective utilization rate and poor cycle stability.
Using an integrated preparation method based on dual network gels, the electrode active material is directly grown on the same dual network gel matrix, the dislocation separation problem between the electrode and the electrolyte is avoided, and an excellent three-dimensional interwoven mesh structure is formed.
It realizes low charge transfer resistance between the electrode and the electrolyte interface, improves the tensile and electrochemical properties of the device, and has excellent cycling stability and efficient charge transfer.
Smart Images

Figure CN115249590B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of energy storage capacitors, in particular to an all-solid-state stretchable supercapacitor based on a double network gel and a preparation method thereof. Background Art
[0002] In recent years, the global warming problem has become increasingly serious due to the greenhouse gas effect produced by the combustion of non-renewable fuels. In addition, non-renewable resources are becoming increasingly depleted. Therefore, it is necessary to seek green renewable energy. Therefore, the storage and conversion of renewable energy has now become a key technology for sustainable development.
[0003] Compared with aqueous supercapacitors, all-solid-state supercapacitors are easy to package and form, have low volatility and flammability, and have no risk of electrolyte leakage. They are not toxic like aqueous electrolytes or flammable like organic electrolytes, and therefore have received increasing research and attention.
[0004] All-solid-state stretchable supercapacitors not only have the advantages of ordinary supercapacitors such as high power density, long cycle life, safety and low cost, but also their good stretchability and flexibility enable them to be well integrated with wearable systems, and have broader application prospects in the field of flexible electronics.
[0005] In the prior art, all-solid-state stretchable supercapacitors, whether based on electrode active materials with specific structural designs, such as wavy films or spirally coiled fibers, or island chain structures with non-stretchable energy storage components connected by stretchable wires on a flexible substrate, are mostly made by coating or laminating electrodes and solid electrolytes. This non-integrated technology is bound to have the disadvantage of poor contact between the electrode and the solid electrolyte interface, which in turn leads to increased charge transfer resistance at the electrode and electrolyte interface, reduced effective utilization of electrode active materials, and poor device cycle stability.
[0006] Chinese patent publication number CN112908726A discloses a method for preparing a double-network all-hydrogel stretchable solid-state supercapacitor, in which the gel electrolyte and gel electrode are prepared separately using the same hydrogel matrix, and then assembled into a "sandwich" structured solid-state supercapacitor by stacking. The interface transmission resistance between the non-integrated supercapacitor electrode and the electrolyte is 0.62Ω. Although the device has stretchability, the granular polyaniline active material grown on the gel matrix skeleton will significantly reduce the overall stretchability. After 3000 charge and discharge cycles, the device's specific capacitance maintains 93% of the initial value.
[0007] Integrated all-solid-state stretchable supercapacitors are different from all-solid-state stretchable supercapacitors. Integrated all-solid-state stretchable supercapacitors have stronger deformation resistance, and they integrate electrodes, electrolytes, etc. on the same stretchable substrate, effectively reducing the charge transfer resistance at the interface between electrodes and electrolytes. Therefore, they can effectively improve the electrochemical performance of the device.
[0008] Chinese patent publication number CN112724565A discloses a method for the integrated preparation of PPy-CoCu-PAA / PEG flexible capacitors. An integrated fully flexible supercapacitor was successfully designed and developed by in situ growing PPy-CoCu on PAA / PEG gel electrolyte. The material prepared by this method has high specific capacitance, excellent energy density and power density, and can be folded and bent, but does not have stretchable properties.
[0009] It can be seen that simultaneously having excellent tensile properties and good electrochemical properties is the key technology that needs to be solved for integrated supercapacitors. Summary of the invention
[0010] The purpose of the present invention is to solve the problems existing in the prior art and to provide an all-solid-state stretchable supercapacitor based on a double network gel and a preparation method thereof. The supercapacitor is based on the same double network gel matrix, and the electrode active material is directly grown on the gel matrix skeleton. There is no problem of dislocation separation between the electrolyte and the electrode. Therefore, the supercapacitor has excellent tensile properties and flexibility, and exhibits good electrochemical properties.
[0011] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0012] The first object of the present invention is to provide a method for preparing an all-solid-state stretchable supercapacitor based on a double network gel, comprising the following steps:
[0013] Step 1, preparing methacrylic acid sulfobetaine monomer;
[0014] Step 2, preparing sodium alginate / acrylamide-methyl methacrylate sulfobetaine copolymer gel SA / P (AM-co-SBMA);
[0015] Step 3: Prepare an integrated all-solid-state stretchable supercapacitor: add 2.2-19.5 mmol of ammonium persulfate to 40-300 ml of 1M hydrochloric acid solution at room temperature, stir evenly to obtain a hydrochloric acid solution of ammonium persulfate; add 1.6-12 mmol of aniline and 0.16-3.6 mmol of p-phenylenediamine to a 1M hydrochloric acid solution at 0-5°C, stir evenly to obtain a hydrochloric acid solution of aniline and p-phenylenediamine, and control the volume of the hydrochloric acid solution of aniline and p-phenylenediamine to be the same as the volume of the hydrochloric acid solution of ammonium persulfate; take the swollen SA / P(AM-co -SBMA) gel discs are ensured to be completely immersed in the hydrochloric acid solution of aniline and p-phenylenediamine, and magnetic stirring is used to make the hydrochloric acid solution of aniline and p-phenylenediamine fully infiltrate the SA / P(AM-co-SBMA) gel sheet, and then the hydrochloric acid solution of ammonium persulfate is slowly added to the gel solution, the reaction temperature is controlled at -5-0°C, and magnetic stirring is maintained for 2-12 hours, and then the gel is repeatedly rinsed and soaked with deionized water to remove impurities, cut into gel blocks and soaked in 1M sulfuric acid solution for 6-24 hours, and the surface liquid is wiped off to obtain an integrated all-solid-state stretchable supercapacitor.
[0016] Furthermore, the step 1 specifically includes:
[0017] 0.01-0.5 mol of 1,3-propane sultone and 0.05-0.2 mol of acetonitrile are uniformly mixed, and then added to a mixture of 0.01-0.5 mol of dimethylaminoethyl methacrylate and 0.1-0.3 mol of acetonitrile, stirred at 20-30° C. for 6-24 hours, and then allowed to stand for 12-60 hours. The obtained white precipitate is repeatedly filtered, centrifuged and washed with acetonitrile and acetone to obtain methacrylic acid sulfobetaine monomer.
[0018] Furthermore, the step 2 specifically includes:
[0019] Acrylamide and methacrylic acid sulfobetaine monomers are added to 0.3 mmol sodium alginate solution, and then 0.01-0.2 mmol N,N-methylenebisacrylamide and 0.01-0.2 mmol ammonium persulfate are added and mixed evenly. The mixture is poured into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization, and then the gel disc is dialyzed with deionized water to remove impurities.
[0020] Furthermore, in the step three, the specific steps of swelling the SA / P (AM-co-SBMA) gel disc are: soaking the SA / P (AM-co-SBMA) gel disc after removing impurities in deionized water for 2-3 days to make it moderately swell, and the diameter of the swollen SA / P (AM-co-SBMA) gel disc is 5 cm and the thickness is 5 mm.
[0021] Furthermore, in the step 3, the gel from which impurities are removed is cut into gel blocks of 1 cm in length and 1 cm in width while maintaining its thickness (the size of the gel blocks is not limited thereto and may also be cut into other sizes), and then immersed in a sulfuric acid solution.
[0022] Furthermore, the molar ratio of acrylamide to methacrylic acid sulfobetaine monomer is between 1:10 and 20:1, and the concentration of sodium alginate is between 0.02 and 0.25 mol / L.
[0023] The second object of the present invention is to provide an all-solid-state stretchable supercapacitor based on double network gel prepared by the above method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The integrated all-solid-state stretchable supercapacitor based on double network gel provided by the present invention effectively solves the problems of dislocation and separation caused by the superposition of multilayer structures of electrodes and electrolytes. Compared with the existing non-integrated supercapacitors, the charge transfer resistance of the electrode and electrolyte interface is only 0.44 ohms. It can be seen that the charge transfer resistance of the electrode and electrolyte interface is reduced by nearly 30% after integration;
[0026] (2) The present invention provides an integrated all-solid-state stretchable supercapacitor based on a double network gel. The SA / P (AM-co-SBMA) double network polymer hydrogel is used as a matrix. Under the conditions of moderate swelling and introduction of p-phenylenediamine, polyaniline is in situ compounded to obtain an integrated all-solid-state stretchable supercapacitor. The polyaniline nanowires grown on the gel matrix skeleton present a three-dimensional interwoven network structure, thereby ensuring that the integrated device has excellent tensile performance. The elongation of the integrated supercapacitor can reach 320%;
[0027] (3) The integrated all-solid-state stretchable supercapacitor based on the double network gel provided by the present invention exhibits excellent cycling stability at 50 μA / cm 2 At a current density of 1.5 Å, the specific capacitance remains 100% of the initial value after 5,500 charge-discharge cycles, and 95% of the initial value after 10,000 charge-discharge cycles.
[0028] Therefore, the present invention has important practical significance and application value for the application of integrated all-solid-state stretchable supercapacitors in flexible and wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the cross-sectional electron microscope scanning structure of the integrated all-solid-state stretchable supercapacitor in the present invention.
[0030] Figure 2 Schematic diagram of the stretching of the integrated all-solid-state stretchable supercapacitor in the present invention: (a) length before stretching; (b) length after stretching.
[0031] Figure 3 Schematic diagram of the charge and discharge curves of the integrated all-solid-state stretchable supercapacitor at different current densities in the present invention.
[0032] Figure 4 Schematic diagram of cyclic voltammetry curves of the integrated all-solid-state stretchable supercapacitor at different scan rates in the present invention.
[0033] Figure 5 A comparison diagram of the Nyquist curves of the integrated all-solid-state stretchable supercapacitor prepared by the present invention and the non-integrated supercapacitor in the prior art.
[0034] Figure 6 The integrated all-solid-state stretchable supercapacitor in the present invention has a current of 50 μA / cm 2 Schematic diagram of the cycling stability curve at current density. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0036] Example 1
[0037] (1) Preparation of methacrylic acid sulfonate betaine monomer: 0.02 mol of 1,3-propane sultone and 0.06 mol of acetonitrile were mixed uniformly, and then added to a mixture of 0.02 mol of dimethylaminoethyl methacrylate and 0.1 mol of acetonitrile, stirred at 20° C. for 12 hours, and then allowed to stand for 12 hours. The obtained white precipitate was repeatedly filtered, centrifuged, and washed with acetonitrile and acetone to obtain methacrylic acid sulfonate betaine monomer;
[0038] (2) Preparation of sodium alginate / acrylamide-methacrylic acid sulfobetaine copolymer gel SA / P (AM-co-SBMA): Add acrylamide and methacrylic acid sulfobetaine monomers in a molar ratio of 1:10 to a 0.1 mmol sodium alginate solution with a concentration of 0.02 mol / L, then add 0.02 mmol N,N-methylenebisacrylamide and 0.02 mmol ammonium persulfate, mix well, and cast the mixture into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization. Then, dialyze the gel disc with deionized water to remove impurities. After cleaning, soak the gel disc in deionized water for 2-3 days to allow it to swell moderately. The swollen SA / P (AM-co-SBMA) gel disc has a diameter of about 5 cm and a thickness of about 5 mm, preparing for the subsequent integrated in-situ growth of polyaniline electrodes.
[0039] (3) Preparation of an integrated all-solid-state stretchable supercapacitor: 4 mmol of ammonium persulfate was added to 70 ml of 1 M hydrochloric acid solution at room temperature, and stirred evenly to obtain an ammonium persulfate hydrochloric acid solution; 2.7 mmol of aniline and 0.5 mmol of p-phenylenediamine were added to a 0°C 1 M hydrochloric acid solution, and stirred evenly to obtain an aniline and p-phenylenediamine hydrochloric acid solution, and the volume of the aniline and p-phenylenediamine hydrochloric acid solution was controlled to be the same as that of the ammonium persulfate hydrochloric acid solution; a swollen SA / P (AM-co-SBMA) gel disc with a diameter of about 5 cm and a thickness of about 5 mm was placed in the aniline and p-phenylenediamine hydrochloric acid solution. The hydrochloric acid solution of diamine was added to ensure that the gel disc was completely immersed in the solution. The solution was stirred magnetically to allow the SA / P (AM-co-SBMA) gel sheet to be fully infiltrated. The hydrochloric acid solution of ammonium persulfate was then slowly added to the gel solution. The reaction temperature was controlled at 0°C and magnetic stirring was maintained for 6 hours. The gel was then repeatedly rinsed and soaked in deionized water to remove impurities. The washed gel was cut into blocks of 1 cm long and 1 cm wide while maintaining its thickness. The cut gel blocks were soaked in 1M sulfuric acid solution for 12 hours. After wiping off the surface liquid, an integrated all-solid-state stretchable supercapacitor was obtained.
[0040] The schematic diagram of the electron microscope scanning structure of the integrated all-solid-state stretchable supercapacitor prepared in this embodiment is shown in FIG. Figure 1 As shown, it can be seen that in the integrated all-solid-state stretchable supercapacitor prepared in this embodiment, the gel electrolyte is located at Figure 1 (a) The middle area shows a three-dimensional porous network structure, where the electrodes are located Figure 1 (a) Upper and lower regions, partial enlarged images of the electrodes are shown in Figure 1 In (b) and (c), it can be seen that the electrode also presents a three-dimensional porous structure, but the pore size is significantly smaller than that of the gel electrolyte, and the polyaniline nanowires grown on the gel skeleton present a three-dimensional interwoven network structure.
[0041] Example 2
[0042] (1) Preparation of methacrylic acid sulfonate betaine monomer: 0.02 mol of 1,3-propane sultone and 0.06 mol of acetonitrile were mixed uniformly, and then added to a mixture of 0.02 mol of dimethylaminoethyl methacrylate and 0.1 mol of acetonitrile, stirred at 20° C. for 12 hours, and then allowed to stand for 12 hours. The obtained white precipitate was repeatedly filtered, centrifuged, and washed with acetonitrile and acetone to obtain methacrylic acid sulfonate betaine monomer;
[0043] (2) Preparation of sodium alginate / acrylamide-methacrylic acid sulfobetaine copolymer gel SA / P (AM-co-SBMA): Add acrylamide and methacrylic acid sulfobetaine monomers with a molar ratio of 20:1 to a 0.1 mmol sodium alginate solution with a concentration of 0.25 mol / L, then add 0.02 mmol N,N-methylenebisacrylamide and 0.02 mmol ammonium persulfate, mix well, and cast the mixture into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization. Then, dialyze the gel disc with deionized water to remove impurities. After cleaning, soak the gel disc in deionized water for 2-3 days to allow it to swell moderately. The swollen SA / P (AM-co-SBMA) gel disc has a diameter of about 5 cm and a thickness of about 5 mm, preparing for the subsequent integrated in-situ growth of polyaniline electrodes.
[0044] (3) Preparation of an integrated all-solid-state stretchable supercapacitor: Add 4 mmol of ammonium persulfate to 80 ml of 1 M hydrochloric acid solution at room temperature and stir to obtain an ammonium persulfate hydrochloric acid solution; Add 3 mmol of aniline and 0.3 mmol of p-phenylenediamine to a 1 M hydrochloric acid solution at 0°C and stir to obtain an aniline and p-phenylenediamine hydrochloric acid solution, and control the volume of the aniline and p-phenylenediamine hydrochloric acid solution to be the same as that of the ammonium persulfate hydrochloric acid solution; Place a swollen SA / P (AM-co-SBMA) gel disc with a diameter of about 5 cm and a thickness of about 5 mm into the aniline and p-phenylenediamine hydrochloric acid solution. The hydrochloric acid solution of ammonium persulfate was added slowly to the gel solution. The reaction temperature was controlled at 0°C and magnetic stirring was maintained for 6 hours. The gel was then repeatedly rinsed and soaked in deionized water to remove impurities. The washed gel was cut into blocks of 1 cm long and 1 cm wide while maintaining its thickness. The cut gel blocks were soaked in 1M sulfuric acid solution for 12 hours. The surface liquid was wiped off to obtain an integrated all-solid-state stretchable supercapacitor.
[0045] The stretching schematic diagram of the integrated all-solid-state stretchable supercapacitor prepared in this embodiment is shown in Figure 2. (The integrated device for the stretching experiment uses a specific mold, so the sample size is different.) It can be seen that the integrated all-solid-state stretchable supercapacitor prepared in this embodiment has an elongation of 320%.
[0046] Example 3
[0047] (1) Preparation of methacrylic acid sulfonate betaine monomer: 0.02 mol of 1,3-propane sultone and 0.06 mol of acetonitrile were mixed uniformly, and then added to a mixture of 0.02 mol of dimethylaminoethyl methacrylate and 0.1 mol of acetonitrile, stirred at 20° C. for 12 hours, and then allowed to stand for 12 hours. The obtained white precipitate was repeatedly filtered, centrifuged, and washed with acetonitrile and acetone to obtain methacrylic acid sulfonate betaine monomer;
[0048] (2) Preparation of sodium alginate / acrylamide-methacrylic acid sulfobetaine copolymer gel SA / P (AM-co-SBMA): Add acrylamide and methacrylic acid sulfobetaine monomers in a molar ratio of 1:1 to a 0.1 mmol sodium alginate solution with a concentration of 0.2 mol / L, then add 0.02 mmol N,N-methylenebisacrylamide and 0.02 mmol ammonium persulfate, mix well, and cast the mixture into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization. Then, dialyze the gel disc with deionized water to remove impurities. After cleaning, soak the gel disc in deionized water for 2-3 days to allow it to swell moderately. The swollen SA / P (AM-co-SBMA) gel disc has a diameter of about 5 cm and a thickness of about 5 mm, preparing for the subsequent integrated in-situ growth of polyaniline electrodes.
[0049] (3) Preparation of an integrated all-solid-state stretchable supercapacitor: Add 5 mmol of ammonium persulfate to 120 ml of 1 M hydrochloric acid solution at room temperature, stir evenly to obtain an ammonium persulfate hydrochloric acid solution; add 3 mmol of aniline and 0.6 mmol of p-phenylenediamine to a 0°C 1 M hydrochloric acid solution, stir evenly to obtain an aniline and p-phenylenediamine hydrochloric acid solution, and control the volume of the aniline and p-phenylenediamine hydrochloric acid solution to be the same as that of the ammonium persulfate hydrochloric acid solution; place a swollen SA / P (AM-co-SBMA) gel disc with a diameter of about 5 cm and a thickness of about 5 mm into the aniline and p-phenylenediamine hydrochloric acid solution. The hydrochloric acid solution of ammonium persulfate was added slowly to the gel solution. The reaction temperature was controlled at 0°C and magnetic stirring was maintained for 6 hours. The gel was then repeatedly rinsed and soaked in deionized water to remove impurities. The washed gel was cut into blocks of 1 cm long and 1 cm wide while maintaining its thickness. The cut gel blocks were soaked in 1M sulfuric acid solution for 12 hours. The surface liquid was wiped off to obtain an integrated all-solid-state stretchable supercapacitor.
[0050] The schematic diagram of charging and discharging of the all-solid-state stretchable supercapacitor prepared in this embodiment at different current densities is shown in FIG. Figure 3 As shown in the figure, it can be seen that the integrated all-solid-state stretchable supercapacitor prepared in this embodiment has good charge and discharge reversibility. 2 Under the condition of current density, it has 4.4mF / cm 2 Surface capacitance.
[0051] Example 4
[0052] (1) Preparation of methacrylic acid sulfonate betaine monomer: 0.02 mol of 1,3-propane sultone and 0.06 mol of acetonitrile were mixed uniformly, and then added to a mixture of 0.02 mol of dimethylaminoethyl methacrylate and 0.1 mol of acetonitrile, stirred at 20° C. for 12 hours, and then allowed to stand for 12 hours. The obtained white precipitate was repeatedly filtered, centrifuged, and washed with acetonitrile and acetone to obtain methacrylic acid sulfonate betaine monomer;
[0053] (2) Preparation of sodium alginate / acrylamide-methacrylic acid sulfobetaine copolymer gel SA / P (AM-co-SBMA): Add acrylamide and methacrylic acid sulfobetaine monomers with a molar ratio of 8:1 to a 0.1 mmol sodium alginate solution with a concentration of 0.02 mol / L, then add 0.02 mmol N,N-methylenebisacrylamide and 0.02 mmol ammonium persulfate, mix well, and cast the mixture into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization. Then, dialyze the gel disc with deionized water to remove impurities. After cleaning, soak the gel disc in deionized water for 2-3 days to allow it to swell moderately. The swollen SA / P (AM-co-SBMA) gel disc has a diameter of about 5 cm and a thickness of about 5 mm, preparing for the subsequent integrated in-situ growth of polyaniline electrodes.
[0054] (3) Preparation of an integrated all-solid-state stretchable supercapacitor: Add 3 mmol of ammonium persulfate to 100 ml of 1 M hydrochloric acid solution at room temperature and stir to obtain an ammonium persulfate hydrochloric acid solution; Add 2 mmol of aniline and 0.4 mmol of p-phenylenediamine to a 1 M hydrochloric acid solution at 0°C and stir to obtain an aniline and p-phenylenediamine hydrochloric acid solution, and control the volume of the aniline and p-phenylenediamine hydrochloric acid solution to be the same as that of the ammonium persulfate hydrochloric acid solution; Place a swollen SA / P (AM-co-SBMA) gel disc with a diameter of about 5 cm and a thickness of about 5 mm into the aniline and p-phenylenediamine hydrochloric acid solution. The hydrochloric acid solution of ammonium persulfate was added slowly to the gel solution. The reaction temperature was controlled at 0°C and magnetic stirring was maintained for 6 hours. The gel was then repeatedly rinsed and soaked in deionized water to remove impurities. The washed gel was cut into blocks of 1 cm long and 1 cm wide while maintaining its thickness. The cut gel blocks were soaked in 1M sulfuric acid solution for 12 hours. The surface liquid was wiped off to obtain an integrated all-solid-state stretchable supercapacitor.
[0055] The schematic diagram of the cyclic voltammetry curves of the integrated all-solid-state stretchable supercapacitor prepared in this embodiment at different scan rates is shown in FIG. Figure 4 As shown, it can be seen that the integrated all-solid-state stretchable supercapacitor prepared in this embodiment has good rate characteristics.
[0056] Example 5
[0057] (1) Preparation of methacrylic acid sulfonate betaine monomer: 0.02 mol of 1,3-propane sultone and 0.06 mol of acetonitrile were mixed uniformly, and then added to a mixture of 0.02 mol of dimethylaminoethyl methacrylate and 0.1 mol of acetonitrile, stirred at 20° C. for 12 hours, and then allowed to stand for 12 hours. The obtained white precipitate was repeatedly filtered, centrifuged, and washed with acetonitrile and acetone to obtain methacrylic acid sulfonate betaine monomer;
[0058] (2) Preparation of sodium alginate / acrylamide-methacrylic acid sulfobetaine copolymer gel SA / P (AM-co-SBMA): Add acrylamide and methacrylic acid sulfobetaine monomers with a molar ratio of 5:1 to a 0.1 mmol sodium alginate solution with a concentration of 0.25 mol / L, then add 0.02 mmol N,N-methylenebisacrylamide and 0.02 mmol ammonium persulfate, mix well, and cast the mixture into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form an SA / P (AM-co-SBMA) gel disc by in-situ polymerization. Then, dialyze the gel disc with deionized water to remove impurities. After cleaning, soak the gel disc in deionized water for 2-3 days to allow it to swell moderately. The swollen SA / P (AM-co-SBMA) gel disc has a diameter of about 5 cm and a thickness of about 5 mm, preparing for the subsequent integrated in-situ growth of polyaniline electrodes.
[0059] (3) Preparation of an integrated all-solid-state stretchable supercapacitor: 3.75 mmol of ammonium persulfate was added to 75 ml of 1 M hydrochloric acid solution at room temperature, and the mixture was stirred to obtain an ammonium persulfate hydrochloric acid solution; 3 mmol of aniline and 0.6 mmol of p-phenylenediamine were added to a 1 M hydrochloric acid solution at 0°C, and the mixture was stirred to obtain an aniline and p-phenylenediamine hydrochloric acid solution, wherein the volume of the aniline and p-phenylenediamine hydrochloric acid solution was controlled to be the same as that of the ammonium persulfate hydrochloric acid solution; a swollen SA / P (AM-co-SBMA) gel disc having a diameter of about 5 cm and a thickness of about 5 mm was placed in the aniline and p-phenylenediamine hydrochloric acid solution. The hydrochloric acid solution of diamine was added to ensure that the gel disc was completely immersed in the solution. The solution was stirred magnetically to allow the SA / P (AM-co-SBMA) gel sheet to be fully infiltrated. The hydrochloric acid solution of ammonium persulfate was then slowly added to the gel solution. The reaction temperature was controlled at 0°C and magnetic stirring was maintained for 6 hours. The gel was then repeatedly rinsed and soaked in deionized water to remove impurities. The washed gel was cut into blocks of 1 cm long and 1 cm wide while maintaining its thickness. The cut gel blocks were soaked in 1M sulfuric acid solution for 12 hours. After wiping off the surface liquid, an integrated all-solid-state stretchable supercapacitor was obtained.
[0060] The non-integrated supercapacitor electrode and electrolyte interface transfer resistance prepared by the preparation method of a double-network all-hydrogel stretchable solid-state supercapacitor disclosed in Chinese Patent Publication No. CN112908726A is 0.62Ω; while the integrated all-solid-state stretchable supercapacitor electrode and electrolyte interface charge transfer resistance prepared in this embodiment is only 0.44 ohm, see Figure 5 ,Depend on Figure 5 It can be seen that the charge transfer resistance at the interface between the electrode and the electrolyte is reduced by nearly 30% after integration.
[0061] In addition, the integrated all-solid-state stretchable supercapacitor prepared in this embodiment has a high conductivity at 50 μA / cm 2 The schematic diagram of the cycling stability curve at a current density of Figure 6 As shown, it can be seen that at 50μA / cm 2 At a current density of , the specific capacitance maintains 100% of the initial value after 5500 charge and discharge cycles, and the specific capacitance still maintains 95% of the initial value after 10000 charge and discharge cycles. The integrated all-solid-state stretchable supercapacitor has excellent cycle stability.
[0062] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing an all-solid-state stretchable supercapacitor based on a double network gel. It is characterized by comprising the following steps: Step 1, preparing methacrylic acid sulfobetaine monomer; Step 2, preparing sodium alginate / acrylamide-methyl methacrylate sulfobetaine copolymer gel SA / P (AM-co-SBMA); Step 3: Prepare an integrated all-solid-state stretchable supercapacitor: add 2.2-19.5 mmol of ammonium persulfate to 40-300 ml of 1 M hydrochloric acid solution at room temperature, stir evenly to obtain a hydrochloric acid solution of ammonium persulfate; add 1.6-12 mmol of aniline and 0.16-3.6 mmol of p-phenylenediamine to a 1 M hydrochloric acid solution at 0-5 °C, stir evenly to obtain a hydrochloric acid solution of aniline and p-phenylenediamine, and control the volume of the hydrochloric acid solution of aniline and p-phenylenediamine to be the same as the volume of the hydrochloric acid solution of ammonium persulfate; soak the SA / P(AM-co-SBMA) gel disc after removing impurities in deionized water for 2-3 days to make it moderately swell, and obtain a swollen SA / P(AM-co-SBMA) gel disc with a diameter of 5 cm and a thickness of 5 mm, and take the swollen SA / P(AM-co-SBMA) The gel disc is ensured to be completely immersed in the hydrochloric acid solution of aniline and p-phenylenediamine, and the hydrochloric acid solution of aniline and p-phenylenediamine is magnetically stirred to fully infiltrate the SA / P(AM-co-SBMA) gel sheet, and then the hydrochloric acid solution of ammonium persulfate is slowly added to the gel solution, the reaction temperature is controlled at -5-0 ℃, and the magnetic stirring is maintained for 2-12 hours, and then the gel is repeatedly rinsed and soaked with deionized water to remove impurities, cut into gel blocks and soaked in 1 M sulfuric acid solution for 6-24 hours, and the surface liquid is wiped off to obtain an integrated all-solid-state stretchable supercapacitor; The integrated all-solid-state stretchable supercapacitor uses SA / P (AM-co-SBMA) double network polymer hydrogel as a matrix. Under the conditions of moderate swelling and introduction of p-phenylenediamine, polyaniline is in situ compounded to obtain an integrated all-solid-state stretchable supercapacitor. The polyaniline nanowires grown on the gel matrix skeleton present a three-dimensional interwoven network structure.
2. The method for preparing a double network gel-based all-solid-state stretchable supercapacitor according to claim 1, characterized in that: The step 1 specifically includes: After 0.01-0.5 mol of 1,3-propane sultone and 0.05-0.2 mol of acetonitrile are mixed evenly, the mixture is added to a mixture of 0.01-0.5 mol of dimethylaminoethyl methacrylate and 0.1-0.3 mol of acetonitrile, stirred at 20-30 °C for 6-24 hours, and then allowed to stand for 12-60 hours. The obtained white precipitate is repeatedly filtered, centrifuged and rinsed with acetonitrile and acetone to obtain methacrylic acid sulfobetaine monomer.
3. The method for preparing a double network gel-based all-solid-state stretchable supercapacitor according to claim 1, characterized in that: The step 2 specifically includes: Acrylamide and methacrylic acid sulfobetaine monomers were added to 0.3 mmol sodium alginate solution, and then 0.01-0.2 mmol N,N-methylenebisacrylamide and 0.01-0.2 mmol ammonium persulfate were added and mixed evenly. The mixture was poured into a polytetrafluoroethylene mold with a diameter of 2 cm and a groove depth of 2.5 mm to form SA / P (AM-co-SBMA) gel discs by in situ polymerization. The gel discs were then dialyzed with deionized water to remove impurities.
4. The method for preparing a double network gel-based all-solid-state stretchable supercapacitor according to claim 1, characterized in that: In the step 3, the gel from which impurities have been removed is cut into gel blocks of 1 cm in length and 1 cm in width while maintaining its thickness, and then immersed in a sulfuric acid solution.
5. The method for preparing a double network gel-based all-solid-state stretchable supercapacitor according to claim 3, characterized in that: The molar ratio of acrylamide to methacrylic acid sulfobetaine monomer is between 1:10 and 20:1, and the concentration of sodium alginate is between 0.02 and 0.25 mol / L.
6. An all-solid-state stretchable supercapacitor based on a double network gel prepared by the method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method for integrally preparing PPy-CoCu-PAA / PEG flexible capacitor
CN112724565A
Porous cross-linked polyaniline electrode material and preparation method thereof
CN106935414A
Preparation method of self-healing flexible solid-state supercapacitor
CN110415997A
Preparation method of dual-network all-hydrogel stretchable solid supercapacitor
CN112908726A